1992
DOI: 10.1111/j.1464-5491.1992.tb01820.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Education: Whose Priorities Are Met?

Abstract: Two hundred Type 2 diabetic patients newly referred to the diabetes centre at a large university teaching hospital were studied over an 8-month period. Patients completed a diabetes knowledge questionnaire, and specified their educational priorities by selecting six diabetes-related topics from a list of 14. After giving 1 h of individual education and using the same list, the educators selected six topics which they considered to be most important for that particular patient to know. Choice of educational pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…The role of diet and physical activity for health, especially in regard to diabetes, are increasingly common media messages that could influence topic knowledge and salience especially for those dealing with a recent diagnosis. Concerns may also be influenced by the type of diabetes treatment received [21]. However, to maintain privacy and anonymity of chat room participants, we were unable to obtain information about individual diabetes diagnosis and treatment status.…”
Section: Discussionmentioning
confidence: 97%
“…The role of diet and physical activity for health, especially in regard to diabetes, are increasingly common media messages that could influence topic knowledge and salience especially for those dealing with a recent diagnosis. Concerns may also be influenced by the type of diabetes treatment received [21]. However, to maintain privacy and anonymity of chat room participants, we were unable to obtain information about individual diabetes diagnosis and treatment status.…”
Section: Discussionmentioning
confidence: 97%
“…Glasgow and Osteen (47) have recently suggested that the evaluation of an education program is often confined to measures of glycemic control and knowledge that is inadequate. Other authors have also suggested that there needs to be more consideration of the beliefs and behavior of people with NIDDM and greater use of education methods addressing patient-centered perspectives, self-efficacy, and empowerment issues (48)(49)(50).…”
Section: Conclusion -This Study Showsmentioning
confidence: 96%
“…Intensive diabetes therapy includes, in addition to intensive insulin treatment, blood glucose home monitoring and intensive patient education 3. Multiple injection therapy has made the treatment of diabetes more flexible, but also imposes greater demands in relation to self‐care of diabetes 4. New devices developed for injecting insulin, such as the insulin pen and a variety of needles, require new skills 5.…”
Section: Introductionmentioning
confidence: 99%